Enhanced catalytic performance for VOCs oxidation on the CoAlO oxides by KMnO4 doped on facile synthesis. (March 2019) - Zhao, Qian; Liu, Qingling; Song, Chunfeng; Ji, Na; Ma, Degang; Lu, Xuebin
Abstract: The MnOx was immobilized on the CoAl mixed oxides (CoAlO) derived from hydrotalcites with various anions (CO3 2−, Cl −, NO3 − and SO4 2− ) using the hydration and impregnation methods. The CoAlO oxides modified by KMnO4 were calcined in air at 300 °C to obtain stable oxides, which could be used as catalysts for VOCs (acetone and ethyl acetate) oxidation. CoAlO with CO3 2− and 30 h of hydration time (CoAlO-C-Mn-30) exhibited a promising catalytic activity (T90 = 173 °C for acetone oxidation; T90 = 175 °C for ethyl acetate), highly superior to CoAlO without KMnO4 modification. The improvement in acetone and ethyl acetate catalytic oxidation was ascribed to the Co 3+ and surface adsorbed oxygen species. The increase of Co 3+ in the CoAlO-C-Mn-30 oxide thanked to the self-decomposition of KMnO4 and reducibility of Co 2+ in the CoAlO oxide during the hydration process. This was also confirmed by XRD and XPS characterization, which showed that Mn cations were enriched on the catalyst surface in the valences of +3 and +4. The catalytic activity of the catalyst remained unchanged in four cycles in the presence of 5.5 vol.% water vapor, which indicated a great potential for industrial application. Graphical abstract: In this work, the MnOx was immobilized on the CoAl mixed oxides (CoAlO) derived from hydrotalcites and enriched on the CoAlO surface in the valences of +3 and + 4. This rendered more surface Co 3+ on the catalyst. The presence of Co 3+ improved the low temperature reducibility and surface oxygen species, which are the main contributors for acetone and ethyl acetate oxidation. Image 1 Highlights: MnOx was immobilized on the CoAlO, which thanked to self-decomposition of KMnO4 and reducibility of Co 2+ of the CoAlO. The catalytic activity of CoAlO and CoAlO-X-Mn was influenced by crystalline structure of the CoAl-X-LDH precursor. The addition of KMnO4 enhanced the Co 3+ amount and adsorbed oxygen species (Oads) of the CoAlO. The CoAlO-C-Mn-30 presented an excellent catalytic activity, which was attributed to the abundance Co 3+ and Oads.